Flaviphenalenones A–C, three new phenalenone derivatives from the fungus Aspergillus flavipes PJ03-11. Issue 6 (10th February 2016) - Zhang, Li-Hua; Feng, Bao-Min; Sun, Yi; Wu, Hong-Hua; Li, Sheng-Ge; Liu, Bing; Liu, Fang; Zhang, Wei-Yang; Chen, Gang; Bai, Jiao; Hua, Hui-Ming; Wang, Hai-Feng; et al.
Graphical abstract: Abstract: Three new phenalenone derivatives, named flaviphenalenones A–C (1 –3 ), together with ten known compounds (4 –13 ) were isolated from solid cultures of a wetland fungus Aspergillus flavipes PJ03-11. Their structures were elucidated on the basis of extensive spectroscopic analysis, and the absolute configuration of compound1 was established by computational electronic circular dichroism (ECD) method. Compounds2 and3 showed stronger inhibitory activities on α-glucosidase than acarbose, and compound1 exhibited strong cytotoxic activities against A549 and MCF-7. In addition, the possible biosynthetic pathways of compounds1 –3 were also proposed.